KIAT MEMENANGKAN PERSAINGAN DI ERA INDUSTRI 4.0 - Amirul Amirul; Danis Wahyu Susanto; Romi Syahrial; Nurlina Nurlina; Prihandono Prohandono (JURNAL ABDIMAS PLJ, 2021)
The most important problems faced by  YAPPA Vocational Hihg Scholl graduatesok is how to find a job after graduating fromvocational education. This is the problem because there is a discrepancy between the curriculum  established by government and the condition that takes palce in the school and its entiremanagement to absorb and imply the curriculum. Several factors that cause this imbalance includes the unavailability of human resources to implement the curriculum optimally, and also due tothe financial condition of school so that the school cannot fulfill the requirements  requested by curriculum. In addition to the school factotr,  parents’ economic factor also determine  learning outcome where people are unable to meet the demands of school to meet the learning requirement.. This is bacouse most of school student at YAPPA Vocational High School come from poor family and orphans. So, Community Service Program from Polytechnic  LP3I Jakarta is expected to contribute to the problem faced by YAPPA Vocational High School graduates in the future.Keyword : Work Preparation, Industrial Age